2016
DOI: 10.1136/rmdopen-2015-000202
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of patient-reported outcome measures (PROMs) for assessing disease activity in rheumatoid arthritis

Abstract: Patient assessment of disease activity in rheumatoid arthritis (RA) may be useful in clinical practice, offering a patient-friendly, location independent, and a time-efficient and cost-efficient means of monitoring the disease. The objective of this study was to identify patient-reported outcome measures (PROMs) to assess disease activity in RA and to evaluate the measurement properties of these measures. Systematic literature searches were performed in the PubMed and EMBASE databases to identify articles repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 55 publications
0
45
0
Order By: Relevance
“…Abstracted data on psychometric properties and study quality were synthesized as others have previously reported . The psychometric properties for each RA disease activity measure received a level of evidence of strong (rating of +++ or ‐ ‐ ‐), moderate (rating of ++ or ‐ ‐), limited (rating of + or ‐), conflicting (rating of ±), or unknown (rating of ?).…”
Section: Methodsmentioning
confidence: 99%
“…Abstracted data on psychometric properties and study quality were synthesized as others have previously reported . The psychometric properties for each RA disease activity measure received a level of evidence of strong (rating of +++ or ‐ ‐ ‐), moderate (rating of ++ or ‐ ‐), limited (rating of + or ‐), conflicting (rating of ±), or unknown (rating of ?).…”
Section: Methodsmentioning
confidence: 99%
“…We provided the level of evidence for each individual FSAM psychometric property, considering all studies evaluating each property and their result using criteria proposed by Hendrikx et al (Table ). Each RA FSAM psychometric property received a level of evidence rating of strong (+++ or − − −), moderate (++ or − −), limited (+ or −), conflicting (±), or unknown (?)…”
Section: Methodsmentioning
confidence: 99%
“…One example of a composite disease activity PROM is the Routine Assessment of Patient Index Data 3 (RAPID3), which is considered the best validated PROM in RA 9 10. In contrast to the Disease Activity Score in 28 joints that includes the erythrocyte sedimentation rate (DAS28-ESR) and the presence of swelling in 28 joints, RAPID3 is solely based on three (subjective) patient-reported domains: physical function, pain and PGA.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been suggested that RAPID3 (similar to other PROMs) could mostly translate factors other than inflammation, such as fatigue, depression or even symptoms driven by comorbidities 11 12. In reality, the question if whether or not RAPID3 truly captures inflammation-driven disease activity in clinical practice is still unanswered 10. If not, this means that if RAPID3 is used to guide treatment decisions on drugs mainly targeting inflammation, clinicians may expose patients to unnecessary risks with only little or no benefit.…”
Section: Introductionmentioning
confidence: 99%